1996
DOI: 10.1046/j.1365-2362.1996.117265.x
|View full text |Cite
|
Sign up to set email alerts
|

Influences of lipid and non‐lipid nutritional parameters on factor VII coagulant activity in normal subjects: the Nove Study

Abstract: Abstract.Community-based studies have suggested that the dietary intake of total fat influences factor VII coagulant activity (FVII c ), a predictor of fatal events from coronary heart disease (CHD). Nevertheless, the question whether the quality of dietary fats, with special reference to fatty acids (FAs), influences FVII c is unsolved. The authors investigated in 90 healthy volunteers living in Nove, a village near Vicenza (northern Italy), the relationships between FVII c and the plasma concentration of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A relationship between total fat intake and FVII c was reported, and a reduction in fat intake resulted in a marked decline in FVII c . An association was found between the proportion of stearic acid in plasma FFA and FVII c (7,8). Stearic acid and the trans FA elaidic acid (18:1 trans), but not oleic acid (9), were found to increase FVII c activation in vitro, and stearic acid has been postulated to activate factor XII, and hence FVII c , by forming a negatively charged contact surface on TAG-rich lipoproteins.…”
mentioning
confidence: 94%
“…A relationship between total fat intake and FVII c was reported, and a reduction in fat intake resulted in a marked decline in FVII c . An association was found between the proportion of stearic acid in plasma FFA and FVII c (7,8). Stearic acid and the trans FA elaidic acid (18:1 trans), but not oleic acid (9), were found to increase FVII c activation in vitro, and stearic acid has been postulated to activate factor XII, and hence FVII c , by forming a negatively charged contact surface on TAG-rich lipoproteins.…”
mentioning
confidence: 94%
“…A positive association between the saturated fatty acid content of phospholipids and FVIIc, and an inverse relationship between linoleic acid and FVIIc was observed. In a similar study, Girelli and coworkers found a positive association between plasma lipid contents of saturated fatty acids, notably stearic acid, and FVIIc (Girelli et al, 1996). Vegetarianism has been studied by two groups and they reached con¯icting conclusions Pan et al, 1993).…”
Section: Diet and Fvii In Epidemiological Studiesmentioning
confidence: 93%
“…These ®ndings demonstrate the importance of FVII in haemostasis. The impact of FVIIc in human thrombogenesis was suggested by the ®nding of positive associations between FVIIc and prothrombin fragment 1 2 (F1 2) (Miller et al, 1996b;Gouin-Thibault et al, 1996), and by the rise in F1 2 that follows infusion of recombinant FVIIa in FVII-de®cient patients . More direct evidence comes from animal experiments showing that inhibition of the TF pathway causes less ®brin formation and thrombogenesis following intimal injuries of the arteries (Speidel et al, 1996;Jang et al, 1995;Arnljots et al, 1997).…”
Section: Physiological Impact Of Fviimentioning
confidence: 99%